A comprehensive pipeline for multi‐resolution modeling of the mitral valve: Validation, computational efficiency, and predictive capability. (5th September 2017) - Drach, Andrew; Khalighi, Amir H.; Sacks, Michael S.
Abstract: Multiple studies have demonstrated that the pathological geometries unique to each patient can affect the durability of mitral valve (MV) repairs. While computational modeling of the MV is a promising approach to improve the surgical outcomes, the complex MV geometry precludes use of simplified models. Moreover, the lack of complete in vivo geometric information presents significant challenges in the development of patient‐specific computational models. There is thus a need to determine the level of detail necessary for predictive MV models. To address this issue, we have developed a novel pipeline for building attribute‐rich computational models of MV with varying fidelity directly from the in vitro imaging data. The approach combines high‐resolution geometric information from loaded and unloaded states to achieve a high level of anatomic detail, followed by mapping and parametric embedding of tissue attributes to build a high‐resolution, attribute‐rich computational models. Subsequent lower resolution models were then developed and evaluated by comparing the displacements and surface strains to those extracted from the imaging data. We then identified the critical levels of fidelity for building predictive MV models in the dilated and repaired states. We demonstrated that a model with a feature size of about 5 mm and mesh size of about 1 mm was sufficient to predict the overall MV shape, stress, and strain distributions with high accuracy. However, we also noted that more detailed models were found to be needed to simulate microstructural events. We conclude that the developed pipeline enables sufficiently complex models for biomechanical simulations of MV in normal, dilated, repaired states. Abstract : While computational modeling of the mitral valve (MV) is a promising approach to improve the surgical outcomes, its geometrically complex structure and lack of the complete in vivo geometric information presents significant challenges in the development of patient‐specific computational models. We developed a novel pipeline for building attribute‐rich computational models of MV of varying fidelity. We established that a medium level of detail is sufficient to predict MV's loaded configuration with high accuracy. However, more detailed models are needed to investigate microscale events.